2010
DOI: 10.1096/fj.10.163063
|View full text |Cite
|
Sign up to set email alerts
|

Yeast profilin complements profilin deficiency in transgenic tomato fruits and allows development of hypoallergenic tomato fruits

Abstract: Gene silencing of Lyc e 1 leads to reduced allergenicity of tomato fruits but impaired growth of transgenic tomato plants. The aim of the study was to restore growth of Lyc e 1‐deficient tomato plants while retaining reduced allergenicity by simultaneous complementation of profilin deficiency by expression of nonallergenic yeast profilin. Transgenic plants were generated and tested by RT‐PCR and immunoblotting;allergenicity of yeast profilin and transgenic fruits was investigated by IgE binding, basophil activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In plant cells, responses to hormones or environmental stresses, along with cell morphogenesis pathways, induce signaling cascades that correlate with the rearrangement/ turnover of actin-based structures [58][59][60]. In this context, ADF and profilin are small actin-binding proteins that control actin dynamics [61,62]; TCTP also interacts with cytoskeletal actin and plays essential roles in cell protection against various stresses [63,64]. Annexins are Ca 2+ -dependent, membranebinding proteins that fasten and possibly hold together biological structures [65]; their expression is under developmental and environmental control.…”
Section: Proteins Associated With Hormone and Cell Wall Metabolismmentioning
confidence: 99%
“…In plant cells, responses to hormones or environmental stresses, along with cell morphogenesis pathways, induce signaling cascades that correlate with the rearrangement/ turnover of actin-based structures [58][59][60]. In this context, ADF and profilin are small actin-binding proteins that control actin dynamics [61,62]; TCTP also interacts with cytoskeletal actin and plays essential roles in cell protection against various stresses [63,64]. Annexins are Ca 2+ -dependent, membranebinding proteins that fasten and possibly hold together biological structures [65]; their expression is under developmental and environmental control.…”
Section: Proteins Associated With Hormone and Cell Wall Metabolismmentioning
confidence: 99%
“…To compensate for the loss of profilin in Lyc e 1 silenced plants, profilin-deficient transgenic tomato plants were complemented with yeast profilin. Analysis of the resulting transgenic plants revealed an almost complete restoration of plant growth and biomass production [18]. Although these experiments demonstrate the feasibility of generating hypoallergenic food even if essential proteins are targeted, consumer acceptance is likely to be low because there are concerns that introducing foreign genes into crop plants may have an unexpected and negative impact on human health.…”
Section: Discussionmentioning
confidence: 93%
“…An aliquot of the supernatant was immediately mixed with SDS/PAGE loading buffer, denatured at 95 °C for 10 min and subjected to a 12.5% SDS/PAGE under reducing conditions. Recombinant Lyc e 1 was expressed and purified as described previously [18]. Separated proteins were blotted onto porablot NCL nitrocellulose membrane (Macherey‐Nagel, Düren, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 In these situations, there was no evidence to support that GM products are more allergenic than their conventional counterparts; in fact, 7 of these studies suggested that the IgE binding properties of the GM products were actually weaker than those of their conventional counterparts, suggesting that the GM products in those studies could be viewed as potentially hypoallergenic. 69,73,91,93,96,103,109,110 We did identify 2 studies involving human ingestion of GM products, but neither demonstrated that ingestion of the GM food was associated with allergy (to Starlink GM corn, disproven by double-blinded, placebo-controlled, food challenge; or to apple with decreased Mal d 1, which noted significantly less symptom development at ingestion by patients allergic to apple). 58,96 Regarding Starlink corn, this product was approved for animal use in the late 1990s, but then somehow made its way into the human food chain and was detected in some products.…”
Section: Discussionmentioning
confidence: 99%